Existence of Resonance Stability of Triangular Equilibrium Points in Circular Case of the Elliptical Restricted Three-Body Problem Under Radiating and Triaxial Primaries (Journal of Informatics and Mathematical Sciences, 2018)
The linear stability of the triangular librations points is studied in the presence of resonance considering both the primaries as radiating and triaxial. The study is carried out for various values of radiation pressure and Triaxiality parameter of both Primaries. It is found that the parametric resonance is only possible at the resonance frequency \(ω_2=1/2\) in circular case.
Keywords: ER3BP; Triangular Libration Points; Resonance; MATLAB 2016